Composite Coatings with Ceramic Matrix Including Nanomaterials as Solid Lubricants for Oil-Less Automotive Applications - Posmyk A. (Archives of Metallurgy and Materials, 2016)
The paper presents the theoretical basis of manufacturing and chosen applications of composite coatings with ceramic matrix containing nanomaterials as a solid lubricant (AHC+NL). From a theoretical point of view, in order to reduce the friction coefficient of sliding contacts, two materials are required, i.e. one with a high hardness and the other with low shear strength. In case of composite coatings AHC+NL the matrix is a very hard and wear resistant anodic oxide coating (AHC) whereas the solid lubricant used is the nanomaterial (NL) featuring a low shear strength such as glassy carbon nanotubes (GC). Friction coefficient of cast iron GJL-350 sliding against the coating itself is much higher (0.18-0.22) than when it slides against a composite coating (0.08-0.14). It is possible to reduce the friction due to the presence of carbon nanotubes, or metal nanowires.